011 An anatomical approach to the immobile tongue. Issue 12 (14th November 2019) - Rajagopal, S; Samra, K; Athauda, D; Porter, MC; Lau, M; Stern, W; Spillane, J; Holmes, P; Roy, A; Howard, R
Abstract : An immobile or fasciculating tongue is an unusual finding in isolation. Its presence generally indicates a problem with the hypoglossal nerve which controls all the intrinsic and extrinsic muscles of the tongue except the palatoglossus and has five segments; the medullary, cisternal, skull base, carotid space and sublingual. This case series discusses five patients who initially presented with isolated hypoglossal nerve palsies. In each patient the lesion localised to a different segment of the nerve with clear imaging confirmation to support their respective causes. The cases (in anatomical order) include hypoglossal nerve damage as a complication of over-shunting in a patient with idiopathic intracranial hypertension, hypoglossal chronic inflammatory demyelinating polyneuropathy, hypoglossal canal fracture, glomus tumour and tongue malignancy. These cases highlight the broad range of differential diagnoses that should come to mind when assessing a patient with poor tongue movement, wasting and or fasciculation. A structured, anatomical approach to lesions of the hypoglossal nerve is fundamental to accurate diagnosis.